Evaluating Fracture Hematoma Reintroduction vs. Non-Reintroduction in Femoral Shaft Fractures: A Single-Blinded Randomized Controlled Trial - Perez, Nike Kier; Sison, Jerome David (Philippine Journal of Orthopaedics, 2025)
Background. Fracture hematoma plays a critical role in bone healing by supplying essential growth factors. However, the original hematoma is often discarded during surgery. The potential benefits of reintroducing fracture hematoma remain unclear. Objective. This study aimed to evaluate the efficacy of fracture hematoma reintroduction in promoting bone union, reducing pain, and improving functional outcomes in patients with closed femoral shaft fractures treated with open reduction and intramedullary nailing. Methodology. A single-blinded randomized controlled trial was conducted, enrolling 18 adult patients with closed femoral shaft fractures. Patients were randomized into two groups: hematoma reintroduction (n = 9) and non-reintroduction (n = 9). The primary outcome was time to bone union, measured using the Radiographic Union Scale in Tibial fractures (RUST). Secondary outcomes included pain (assessed using the Visual Analog Scale) and functional outcomes (evaluated with the Lower Extremity Functional Scale) at six, 12, and 24 weeks postoperatively. Statistical analysis included ANOVA and multivariable regression. Result. At six weeks, the hematoma reintroduction group showed a significantly higher mean RUST score compared to the non-reintroduction group (p = 0.022). However, by 12 weeks (p = 0.108) and 24 weeks (p = 0.241), the difference between the groups was no longer statistically significant. Both groups demonstrated similar improvements in pain and functional outcomes over time. No complications were reported in either group. Conclusion. While hematoma reintroduction may enhance early bone healing, the long-term outcomes in terms of bone union, pain, and function are comparable between the two treatment approaches. Hematoma reintroduction is a well-tolerated intervention, with no observed complications.